$ A = \frac{1}{1.2} + \frac{1}{3.4} + \frac{1}{5.6} + ... \frac{1}{99.100} \\ = \frac{1}{1} - \frac{1}{2} + \frac{1}{3} - \frac{1}{4} + ... + \frac{1}{99} - \frac{100} \\ = \left (\frac{1}{1} +\frac{1}{2} + \frac{1}{3} + \frac{1}{4} + ... + \frac{1}{99} + \frac{1}{100} \right ) - 2\left ( \frac{1}{2} + \frac{1}{4} + ... +
\frac{1}{100} \right) \\ = \left (\frac{1}{1} +\frac{1}{2} + \frac{1}{3} + \frac{1}{4} + ... + \frac{1}{99} + \frac{1}{100} \right ) - \left (\frac{1}{1} +\frac{1}{2} + ... + \frac{1}{50} \right ) \\ = \frac{1}{51} +\frac{1}{52} + \frac{1}{53} + \frac{1}{54} + ... + \frac{1}{99} + \frac{1}{100} $
Ez